Financial reporting quality and investment efficiency: A transnational evidence - Muhammad Azhar Khan; Nabeel Safdar; Wajiha Manzoor (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
In developed markets, the connection between financial reporting quality (FRQ) and enhanced investment efficiency is well-documented. However, it remains uncertain whether this relationship holds true in emerging, frontier, and various other markets. This research probes into this relationship across 18,231 publicly listed firms spanning thirty- six countries worldwide, encompassing various market categories. Comprehensive accounting data is gathered for publicly traded firms from 2009 to 2023, spanning 40 different industries in these markets. We used Stata and employed fixed-effects regression analysis, augmented by alternative proxies and robustness investigation, causal connections are explored. The endogeneity concerns are addressed using 2SLS regression analysis. The findings disclose a positive influence of FRQ on investment efficiency not only in developed markets but also across emerging, frontier, and other markets. Furthermore, our analysis of over- and under-investment scenarios highlights a significant relationship between FRQ and investment efficiency in both contexts. These findings expand the current body of knowledge, indicating that the relationship between FRQ and investment efficiency extends beyond developed markets to include emerging, frontier, and other markets with varied reporting standards and financial environments.
Keywords: 330; Financial reporting quality; investment efficiency; modified Jones model; emerging markets; developed markets; frontier markets